Adutiškis – Kamojys habitat: linguistic identity in Lithuanian and Belarusian periphery - Urbanavičienė, Jolita (Kalbotyra, 2011)
The surroundings of Adutiškis (district of Švenčionys, Lithuania) and Kamojys (district of Pastovys, Belarus) are analysed in this article as an integral habitat which has lived, until the last decade of the 20th century, in the conditions of intense Lithuanian and Belorussian bilingualism. The current borderline of Kamojys subdialect which includes a circle of only several kilometres around Adutiškis is mapped with reference to the material of the Archive of Dialects of the Institute of the Lithuanian Language and to the records collected by the author, and the final stage of Lithuanian-Belorussian bilingualism is located in the subdialect itself. The author analyses the linguistic identity of the informants born in 1925-1940, in the background of Polonization, Russification and finally in conditions of dominance of the Lithuanian language. She accentuates the characteristics of the linguistic identity of inhabitants of Adutiškis – Kamojys habitat: 1) the inhabitants are bilingual, fluent in Lithuanian and local Belorussian languages; this binary system is interfered by the Polish and the Russian; 2) the linguistic identity is changing constantly: it adapts itself to the political conditions of the region and the social needs of the inhabitants; 3) the declared identity does not always coincide with the language used; a part of inhabitants do not indicate any identity at all. The article analyses the main factors related to the private sphere (family) and to the public life (education, religion, village community, administrative authority) which had a major impact on the formation of the linguistic identity during the second half of the 20th century. Three main stages of formation of the linguistic identity are singled out which can be represented in the following scheme: ethnic self-consciousness (family) → linguistic patriotism (school, church) → social control (village community, administrative authority).